IMPLEMENTASI KEGIATAN SHALAT DHUHA BERJAMAAH DALAM MEMBENTUK KARAKTER SISWA DI MADRASAH TSANAWIYAH NEGERI BATU - Adinda Annisa Darman; Azhar Haq; Muhammad Sulistiono (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
Dhuha prayer which is implemented when people are busy with worldly activities will be the formation of student character, and very much wisdom is contained in it. The time of Dhuha prayer is an extraordinary time to deal with and build a personal relationship with God, so that it is expected to get special attention and love from Him. By implementing the Dhuha prayer in congregation, students will get used to doing it, then the activity will be embedded in the heart and soul, so it becomes a tradition of habits that are difficult to leave behind in their lives. More than that, Dhuha prayer will also shape Islamic character and discipline in students. Based on these explanations, the formation of student character can be done through supportive madrasa activities; an effective, efficient and fun curriculum, as well as a madrasah culture that is applied in MTs Negeri Batu which always carried out regularly in the school environment. The implementation of the Dhuha prayer activities in congregation in forming of student characters can be done through exemplary attitudes. In accordance with the results of observations by the researcher, the teachers always showed an exemplary attitude to the students - the students as well as greeting, shaking hands, applying 4S (smile, greetings, greetings, courtesy). With follow-up in the implementation of the Dhuha prayer activities in the congregation, it can show the development and formation of student characters outside the school environment.